Application of the finite element method in Dentistry - Piccioni, Máyra Andressa R. V. [UNESP]; Campos, Edson Alves [UNESP]; Saad, José Roberto Cury [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP]; Galvão, Marília Regalado [UNESP]; Dantas, Andrea Abi Rached [UNESP] (My University, 2013)
The finite element method (FEM) involves a series of computational procedures to calculate the stress in each element, which performs a model solution. Such a structural analysis allows the determination of stress resulting from external force, pressure, thermal change, and other factors. This method is extremely useful for indicating mechanical aspects of biomaterials and human tissues that can hardly be measured in vivo. The results obtained can then be studied using visualization software within the FEM environment to view a variety of parameters, and to fully identify implications of the analysis. Objective: An overview to show application of FEM in dentistry was undertaken. Literature review: This paper shows the basic concept, advances, advantages, limitations and applications of finite element method (FEM) in dentistry. Conclusion: It is extremely important to verify what the purpose of the study is in order to correctly apply FEM.
Keywords: Finite element analysis; Models; Dentistry